Strategi Kepala Sekolah Dalam Penerapan Pembelajaran Era Digital Di Sekolah Nadrisatul Ikbar - Inom Nasution; Ayu Azhari; Intan Ramadhani; Anggi Gusrina; Zainur Rozzaqiyah; M. Ikhsan; Razak Hadinata (JUPE : Jurnal Pendidikan Mandala, 2022)
his study aims to determine the principal's strategy in implementing digital era learning in MadrisatulIkbar schools. The research approach used in this study is a qualitative approach. This study is qualitative in nature with the main problem of the principal's strategy. The method used in this research is the method of observation and interviews with the principal. From the results of data analysis, it is known that in teaching and learning activities in this digital era there are still many who do not understand. While the factors that cause students to participate less in learning activities in this digital era are internal and external factors where internal factors that come from within students are the lack of awareness that students will understand the importance of using digital for learning. Meanwhile, external factors are factors that come from outside of students, namely family, playground, and the surrounding environment.